PEMANFAATAN LIMBAH AIR KELAPA (Cocos nucifera L.) SEBAGAI PEMBUATAN KECAP MANIS RUMAHAN - Rina Kurniaty; Risa Nursanty (Universitas Ubudiyah Indonesia, 2026)
Limited public awareness regarding the potential of coconut water as a raw material for food products has resulted in this waste not being utilized optimally. Meanwhile, sweet soy sauce is a popular food product in Indonesia, typically made from soybeans. However, the availability of soybeans as a raw material is often constrained by competition with the tofu and tempeh industries, as well as relatively high costs. This community service activity aimed to introduce the utilization of coconut water waste for producing homemade sweet soy sauce, a project carried out by housewives in Gampong Sukaramai, Baiturrahman District, Banda Aceh. The implementation involved demonstrating the process of making homemade sweet soy sauce from coconut water. This initiative serves as a means to support the livelihoods of low-income community members and to enhance the knowledge of housewives regarding the processing and utilization of coconut water waste obtained from local coconut vendors in the Gampong Sukaramai area. Furthermore, the activity aims to foster interest among housewives in independently producing homemade sweet soy sauce using affordable and easily accessible local ingredients. Keywords: Waste coconut water, cocos nucifera, sweet soy sauce, home-based product